Personal features and management activities related to cattle welfare (Agro Productividad, 2021)
Objective: To describe the personal features, as well as the management activities related to cattle welfare in Loma Bonita, Oaxaca, Mexico.Design/Methodology/Approach: This is a cross-sectional, descriptive, and quantitative study. The sampling was non-probabilistic for convenience. Between December 2019 and March 2020, a questionnaire was applied to 27 farmers.Results: The average age of the ranchers is 44.6 years; 55.6% have more than 20 years of experience; 25.9% herd their cattle using a stick; 48.1% do not disinfect the udders; and 25.1% do not wash their hands during milking.Study Limitations/Implications: The results and conclusions are limited to the sample used in the present study. Therefore, extending them to all livestock farmers in the municipality would require a broader study that considers statistical techniques of probabilistic sampling.Findings/Conclusions: There are management activities outside the parameters established by the appropriate sanitary and welfare practices of cattle. However, the personal features indicate the existence of conditions related to the livestock activity in Mexico, that encourage participants to propose and carry out programs, plans, and strategies aimed at promoting and applying practices on animal welfare, thereby improving the productive, reproductive and profitability parameters.